Analisis Pengaruh Biaya Produksi Terhadap Laba Kotor : Literature Review Artikel Terindeks Sinta - Aisyah Aisyah; Lia Nurjanah; Muhamad Ardhi Maolana; Tiara Anggini; Rachmat Agus Santoso (Universitas 45 Surabaya, 2024)
Every company aims to achieve a large gross profit because it has a direct impact on net profit and overall business continuity. A small gross profit can result in a small net profit, which can jeopardize the company's ability to maintain its operations. In addition, gross profit figures are critical for evaluating a company's performance and forecasting future cash flows. . A significant gross profit is expected by every company, especially since gross profit has a direct impact on the company's net profit. Therefore, companies strive for a large gross profit to ensure financial stability and growth. If the gross profit is low, then the net profit will also be affected, and this may threaten the viability of the company. In addition to being a financial indicator, the figures in gross profit can also be used to evaluate company performance and project future cash flow. This study aims to analyze the effect of production costs on the gross profit of a company in various industries. The method applied in this research is a qualitative descriptive method used by conducting a literature review of articles indexed by Sinta in 2018-2024. The results of the analysis show that production costs have a significant effect on gross profit with low production costs causing a decrease in production costs, goods sold and an increase in gross profit for the company.